Framing and social movements - Caiani, Manuela (Discourse studies, 2023)
This article explores the notion and method of discourse and frame analysis in social movement studies. Different cases of frame analysis applied to various types of social movements and contentious politics in Europe are used to illustrate the argument. As stressed in the introduction to this special issue, although the concept of frame and framing is used in several disciplines and approaches in the cognitive, language and social sciences, research on social movements still presents some gaps. One is the prevalent application of frame analysis approach to progressive left wing movements, leaving aside actors on the Right. A second weakness is the scarcity of empirical research combining the micro (i.e. activists) and meso (i.e. organizations) level of framing and exploring dynamics of frame ‘(dis-)alignment’. Third, there is mainly a focus on the framing of national rather than transnational contention, although as this article shows, social movement research is increasing on this regard. The fourth weakness is the scarcity of applications of framing and frame analysis to collective actors and policies - a promising line of research to which social movement studies could make valuable contributions. This article will address these issues to highlight promising venues of research and application in social movement studies.